2011
DOI: 10.1002/pola.24524
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli‐responsive micelles of amphiphilic AMPS‐b‐AAL copolymers in layer‐by‐layer films

Abstract: Aqueous reversible addition‐fragmentation chain transfer polymerization was used to synthesize poly(N‐[3‐(dimethylamino)propyl]acrylamide) (PDMAPA) cationic homopolymers and micelle‐forming, pH‐responsive, amphiphilic diblock copolymers of poly(sodium 2‐acrylamido‐2‐methyl‐1‐propanesulfonate‐block‐N‐acryloyl‐L‐alanine) (P(AMPS‐b‐AAL)). At low pH, the AAL blocks are protonated rendering them hydrophobic, whereas the AMPS blocks remain anionically charged because of the pendant sulfonate groups. Self‐assembly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…5(D)] are prepared at the four cases of polymerization‐induced self‐assembly, respectively. Clearly, this conclusion is very similar with those reported in the self‐assembly of block copolymer in the block‐selective solvent 39, 43, 62, 63. That is, reducing the hydrophilic block typically either poly(acrylic acid) or poly(ethylene oxide) while fixing the hydrophobic polystyrene block leads to the morphological transition from micelles to rods to vesicles to LCMs.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…5(D)] are prepared at the four cases of polymerization‐induced self‐assembly, respectively. Clearly, this conclusion is very similar with those reported in the self‐assembly of block copolymer in the block‐selective solvent 39, 43, 62, 63. That is, reducing the hydrophilic block typically either poly(acrylic acid) or poly(ethylene oxide) while fixing the hydrophobic polystyrene block leads to the morphological transition from micelles to rods to vesicles to LCMs.…”
Section: Resultssupporting
confidence: 87%
“…Second, the size of the block copolymer particles generally increases with the insoluble P4VP block extension during the dispersion RAFT polymerization, whereas the particle morphology transition occurs only when a macro‐RAFT agent with a very short chain length (PS 9 ‐CTA) is employed. In the block copolymer self‐assembly in the block‐selective solvent, it is generally found that increasing the hydrophobic block leads to morphological transition from spheres to rod‐like or vesicular structure,39, 43, 62, 63 which is somewhat different from the present polymerization‐induced self‐assembly.…”
Section: Resultsmentioning
confidence: 72%
“…Subsequently, the anionic poly(sodium 2‐acrylamido‐2‐methyl‐1‐propanesulfonate) micelle shells were ionically cross‐linked with a RAFT‐synthesized cationic homopolymer of either poly( N ‐[3‐(dimethylamino)propyl]acrylamide) or poly( N,N ‐dimethylaminoethyl methacrylate) (Scheme b) 125. McCormick and co‐workers126 also used the pH‐responsive micelles of poly(sodium 2‐acrylamido‐2‐methyl‐1‐propanesulfonate)‐ b ‐poly(A‐( L )Ala‐OH) in layer‐by‐layer films. Self‐assembly resulted in the formation of core shell micelles consisting of hydrophobic cores of poly(A‐( L )Ala‐OH) and negatively charged shells of poly(sodium 2‐acrylamido‐2‐methyl‐ 1‐propanesulfonate).…”
Section: Cross‐linked Block Copolymer Micellesmentioning
confidence: 99%
“…15. [203,587] 357 [357] 358 [582] 356 [239] 353 [222] 352 [222] 354 [236] 355 [427] 359 [170] 360 [533] 368 [292] 366 [486] 367 [423] 369 [58] 370 [383] 371 [245,246] 372 [464] AMPS Ϫ ϩ ϩ Ϫ ϩ ϩ Ϫ 363 [245,246] 361 [328] 362 [328] 364 [289] 365 [383] Ϫ Fig. 8.…”
Section: Monomers With Reactive Functionalitymentioning
confidence: 99%